Pieces for Development : Policy Notes for Chile - World Bank (World Bank, Washington, DC, 2021)
There is no doubt that more sustainable, resistant, and beneficial growth would benefit Chile and its inhabitants. However, this is a difficult and complex issue, with several interconnecting pieces and many different opinions about the best way to achieve this. At the same time, the experience of other countries shows that certain pieces must be in their place in order to achieve this objective. Chile has incorporated several pieces in this puzzle. However, some critical pieces are still needed in order to overcome this challenge. These notes seek to make recommendations about what some of those pieces can be and how to integrate them to complete the puzzle of Chile’s development.